GCMS ANALYSIS OF BIOACTIVE COMPOUNDS OF CHINESE BEAT LEAVES (Peperromia pellucida) WITH EXTRACTION APPLICATION USING SOXHLET ATION METHOD - Armansyah Maulana Harahap; Nila Zusmita Wasni; Indra Priawan M (JBIO: jurnal biosains (the journal of biosciences), 2022)
Chinese betel leaf (Perperomia pellucida) is generally widely used as a medicinal plant. Many people use Chinese betel leaf as a traditional medicine based on natural ingredients which are believed to be able to treat various diseases with fewer side effects than synthetic drugs. In general, China betel leaf has several secondary metabolites, generally flavonoids, steroids, alkaloids and terpenoids. However, in testing for secondary metabolites, there is still no clear description of the plant parts taken. So this study aims to determine the secondary metabolites in the young leaves of Chinese betel (Peperromia pellucida) by gas chromatography. The results obtained based on the GCMS analysis contained 18 secondary metabolites. Phytol, 2,3-BIS (4-(CA RBOXYMETHYL) PHENYL) BENZO [B] FURAN, and 6-ALLYL-4,5 -DIMETHOXY- 1,3-BENZOD IOXOLE are the 3 highest bioactive com pounds based on the percentage of content.